The Correlation between Body Fat Distribution and Medial Tibiofemoral Joint Space Width in Obese Knee Osteoarthritis Patients - Herikurniawan Herikurniawan; Harry Isbagio; Pradana Soewondo; Nyimas Diana; Siti Setiati (Indonesian Journal of Rheumatology, 2017)
Background: Obesity is a major risk factor for knee osteoarthritis. The relationship between obesity and OA may not be simply due to a mechanical factor. Evidences suggest that metabolic factors related to body fat play important roles, but the specific type of fat that contributes to OA is unclear. The objective of this study was to examine the possible correlation between body fat distribution with knee OA.Methods: This study was a cross sectional study of OA patients with obesity visiting the Rheumatology and Geriatric-Internal Medicine clinics at Cipto Mangunkusumo Hospital between January-March 2016. Data was collected by consecutive sampling. Knee OA was diagnosed from clinical and radiologic evaluation based on American College of Rheumatology 1986 criteria. Body fat distribution was measured by bioelectrical impedance analysis (BIA). Conventional radiography of the knee was used to evaluate jointspace narrowing (JSN). The correlation between body fat distribution and joint space width was analyzed by bivariate analysisResult: A total of 56 subjects were recruited, majority were women (73.2%). Median visceral fat was 12% (7.5-16.5), median subcutaneous fat was 30.2% (16.5-37.9), and median visceral to subcutaneous fat ratio was 0,40 (0,26-0,80). The mean medial tibiofemoral joint space width was 2.34 mm (SD 0.78). Bivariate analysis revealed a correlation between visceral fat and medial tibiofemoral joint space width (r: -0,474 p: < 0,001). There is no correlation between subcutaneous fat and medial tibiofemoral joint space width (r: -0,187 p:0,169); and visceral to subcutaneous fat ratio and medialtibiofemoral joint space width (r: -0,225 p: 0,09).Conclusion: Visceral fat is correlated with medial tibiofemoral joint space width (r: -0.474 p: < 0.001). There is no correlation between subcutaneous fat, and visceral to subcutaneous fat ratio, with medial tibiofemoral joint space width.Keywords: Osteoarthritis, obesity, visceral fat, subcutaneous fat, visceral to subcutaneous fat ratio, medial tibiofemoral joint space width